Analysis of Bullet Train Project Using CPM and PERT (International Journal of Innovative Research in Computer Science & Technology, 2022)
One of the most significant tools for project  planning and management is the Critical Path Method  (CPM), as well as the Project Evaluation and Review  Technique (PERT). When the time required or anticipated to  perform specific activities is unclear, PERT is a project  management method. CPM is a method for planning  activities in which the amount of time required to accomplish  the project is presently known. CPM is a step-by-step project  management strategy that keeps processes and projects on  track by focusing on important tasks. The Critical Route is  the shortest approach to finish any project by following one  path across all connected operations. The goal of this  research is to examine the whole bullet train project, its  critical activities and interdependencies, as well as the  precedence connection between them. The authors of this  research article examine the use of CPM and PERT  calculations on bullet train projects. Using CPM we are  studying the critical activities which can affect the project  completion and using PERT authors are analyzing the  estimated time for project completion.
Keywords: Bullet Train; Critical Path Method; Operation Research; Program Evaluation and Review Technique (PERT)